VAR modeling for dynamic semiparametric factors of volatility strings - Ralf Brüggemann; Wolfgang Karl Härdle; Julius Mungo; Carsten Trenkler (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
The implied volatility of a European option as a function of strike price and time to maturity forms a volatility surface. Traders price according to the dynamics of this high dimensional surface. Recent developments that employ semiparametric models approximate the implied volatility surface (IVS) in a finite dimensional function space, allowing for a low dimensional factor representation of these dynamics. This paper presents an investigation into the stochastic properties of the factor loading times series using the vector autoregressive (VAR) framework and analyzes associated movements of these factors with movements in some macroeconomic variables of the Euro-economy.
Keywords: C14; C32; 330; Implied volatility surface; dynamic semiparametric factor model; unit root tests; vector autoregression; impulse responses.